2019
DOI: 10.1037/sah0000127
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and causes of the use of noun-based mental disorder labels.

Abstract: This research investigated (a) the role of empathy and stigmatizing attitudes in the use of noun labels applied to people with psychological disorders (e.g., John is a schizophrenic), and (b) whether depicted violence increases such usage. In Study 1, undergraduate participants (N = 308) read two mock newspaper stories in counterbalanced order: one depicting a man with schizophrenia committing a nonviolent crime and one depicting a man with schizophrenia committing a highly violent crime. Participants then sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…These findings are largely discordant with past literature, which has shown that noun labels both promote stigma (Granello & Gibbs, 2016; Penn & Nowlin-Drummond, 2001) and result from stigmatizing beliefs (Carnaghi et al, 2008; Howell et al, 2014; Howell & Woolgar, 2013) or low empathy (Howell et al, 2014; Krzyzanowski et al, 2019). Notably, however, some previous work has failed to find differences between person-first and noun labels (e.g., Martinelli et al, 2020), as in the current studies.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…These findings are largely discordant with past literature, which has shown that noun labels both promote stigma (Granello & Gibbs, 2016; Penn & Nowlin-Drummond, 2001) and result from stigmatizing beliefs (Carnaghi et al, 2008; Howell et al, 2014; Howell & Woolgar, 2013) or low empathy (Howell et al, 2014; Krzyzanowski et al, 2019). Notably, however, some previous work has failed to find differences between person-first and noun labels (e.g., Martinelli et al, 2020), as in the current studies.…”
Section: Discussioncontrasting
confidence: 64%
“…Analysis of news coverage suggests that noun labels for mental illness are used preferentially for “undesirable social elements” (e.g., criminals), while person-first labels are reserved for non-criminals and children (Carnaghi et al, 2008). Additionally, priming the notion that people with mental illness are violent influences how we choose to describe those people: Premodified noun labels are preferred over person-first labels for people with schizophrenia who are depicted as violent, and lower empathy, greater endorsement of stigmatizing views about mental illness, and dehumanization predict noun label preference (Krzyzanowski et al, 2019). Similarly, the belief that fixed natural causes predetermine mental illness (Carnaghi et al, 2008; Howell et al, 2014; Howell & Woolgar, 2013), low empathy, and negative attitudes about mental illness (Howell et al, 2014) predict noun label preference, while induced compassion reduces this preference (Howell & Woolgar, 2013).…”
Section: Gendermentioning
confidence: 99%
“…This is an area that requires further research with respect to dehumanisation. Of relevance, when research participants were asked to read a news article depicting a violent crime depicted by a man with a diagnosis of schizophrenia, they were much more likely to select noun-labelled headlines (e.g., 'Schizophrenic Snaps') than personfirst ones (e.g., 'Person with Schizophrenia Snaps'), and this was mediated by dehumanising attitudes (Krzyzanowski, Howell and Passmore, 2017). However, another experimental intervention designed to reduce dehumanisation of people with obesity by presenting textual information on its complex causes was unsuccessful, as it may have reinforced existing norms that most people already dehumanise obesity, thus legitimising discriminatory attitudes (Kersbergen and Robinson, 2019).…”
Section: Insert Table II Here Discussionmentioning
confidence: 99%
“…Rai et al , 2017), these types of process may also be relevant to health, criminal justice and social care policy decisions. Subtle dehumanisation of people with mental health problems, for example, predicts increased public social distancing and perceptions of dangerousness (Martinez et al , 2011; Martinez, 2014; Krzyzanowski et al , 2017); blatant dehumanisation of people with obesity predicts public support for discriminatory policies (Kersbergen and Robinson, 2019); whilst dehumanisation of people with alcohol use disorders by healthcare workers has been associated with negative outcomes, such as reduced value paid to patient consent and pain when making a medical decision related to their treatment (Fontesse et al , 2021). Policymakers may take advantage of public perceptions towards out-groups to justify difficult political choices, subsequently reinforcing and maintaining the social contexts that originally shaped those attitudes (Harris, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation